BCD Addition without Carry Propagation - A. Sreekumar, Sukrith B, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Binary Coded Decimal addition is less used due to the computational overhead pertaining to it. We propose an algorithm to reduce the computational overhead caused by removing carry propagation time delay by doing a prefixed set of instructions for a block of 64-bit digits, speeding up the computation up by four times in the ideal case.